Specific Immunotherapy in a Murine Model of Grass Pollen (Phl p5b)-Induced Airway Inflammation - Stiehm, Matthias; Peters, Marcus (Frontiers in Allergy, 2021)
Background Use of ovalbumin as a model allergen in murine models of allergic asthma is controversially discussed, since it is not an aeroallergen and sensitization can only be achieved by using strong Th2 inducing adjuvants. Therefore, in this study a murine model of asthma has been established in which sensitization against the major grass pollen allergen Phl p5b was performed without using Alum. We used this model for specific immunotherapy. Methods Female, 5-6 week old mice were sensitized by six subcutaneous injections of 20 g Phl p5b followed by four provocations to induce allergic airway inflammation. For desensitization 1 mg of Phl p5b was injected subcutaneously during allergen challenge for one to a maximum of four times. Three days after the last challenge the allergic immune response was analyzed. Results Sensitized and challenged animals showed a significant infiltration of eosinophils into the airways and the production of IL-5 by in vitro re-stimulated splenocytes could be detected. Furthermore, hyperresponsiveness of the airways was verified by invasive measurement of airway resistance in methacholine challenged animals. Desensitized animals showed a significant reduction of all parameters. Conclusion In this study a murine model of asthma has successfully been established by sensitization against the clinical relevant allergen Phl p5b without using Alum. Subcutaneous injection of allergen dose dependently led to desensitization of sensitized mice. We suggest that this model is useful to study adjuvant effects of immune modulatory substances on immunotherapy without interference of aluminium hydroxide.